2016
DOI: 10.3390/jcm5090076
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of TGFβ1 Activity in Cancer and Its Influence on the Quality of Anti-Tumor Immunity

Abstract: TGFβ1 is a pleiotropic cytokine that exhibits a variety of physiologic and immune regulatory functions. Although its influence on multiple cell types is critical for the regulation of numerous biologic processes in the host, dysregulation of both TGFβ1 expression and activity is frequently observed in cancer and contributes to various aspects of cancer progression. This review focuses on TGFβ1’s contribution to tumor immune suppression and escape, with emphasis on the influence of this regulatory cytokine on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 158 publications
2
33
0
Order By: Relevance
“…In addition, it was aberrantly activated in the late-stages of tumorigenesis and the dysregulation of TGFβ1 signaling pathway contributed to various aspects of cancer progression [36,37] . Recently, studies indicated that TGFβ1 greatly participated in numerous immune regulatory functions, such as tumor immune suppression and escape [38] . It was also signi cantly associated with the function of kinds of TICs, such as tumor-associated macrophages [39] , dendritic cells [40,41] , neutrophils [42] , T cells [43] and natural killer cells [44] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was aberrantly activated in the late-stages of tumorigenesis and the dysregulation of TGFβ1 signaling pathway contributed to various aspects of cancer progression [36,37] . Recently, studies indicated that TGFβ1 greatly participated in numerous immune regulatory functions, such as tumor immune suppression and escape [38] . It was also signi cantly associated with the function of kinds of TICs, such as tumor-associated macrophages [39] , dendritic cells [40,41] , neutrophils [42] , T cells [43] and natural killer cells [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Further inhibitory mechanisms include ownregulation of costimulatory molecules thus limiting CTL activation, and secretion of immune-modulating factors. TGF-β, for example, promotes regulatory functions in dendritic cells and macrophages and directly inhibits T cell function 93 . Restoration of anti-tumor immunity via engineering antigen-specific T cells that are resistant to TGF-β is one hypothesis that is currently being explored (NCT00368082) 94 .…”
Section: The Limits Of Success For Adoptive T Cell Therapymentioning
confidence: 99%
“…Increased expression of TGFβ1 is a particular feature of the immunosuppressive tumor microenvironment (4) and has been studied extensively as part of a prospective clinical trial (7). During tumor progression, it becomes a stimulatory molecule that promotes immune evasion, growth, invasion, and metastasis by tumor cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the clinical therapeutic regimen for ccRCC has transitioned from a non-specific immune approach to immunotherapeutic strategies. With the clinical application of immunotherapy agents, such as nivolumab (anti-PD-1), the survival of patients with 7 infiltration as stromal and immune scores, and combined the stromal and immune scores as the ESTIMATE score (16).…”
Section: Introductionmentioning
confidence: 99%